Understanding Basics Holography: Review Principle and Recording Technique of Holography - Irsad Tio Majid (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2020)
In this article, we review the basics of holography. Starting to knowing the description of holography, mathematical processing, etc. That also include the principle physics phenomenon in Optical field, the trajectory (Technique) hologram, and the difference about optical holography and digital holography. Holography Technology had been applied to much various cases.